
1. a^{m}.a^{n} = a^{m+n}.
2. a^{m}/a^{n} = a^{mn}. 3. (a^{m})^{n} = a^{mn}. 4. a^{0} = 1. 5. Öa * Öa = a. 6. Öa = a^{1/2}. 7. (a+b)^{2} = a^{2} + 2ab + b^{2}. 8. (ab)^{2} = a^{2}  2ab + b^{2}. 9. (a+b)^{2}  (ab)^{2} = 4ab. 10. (a+b)^{2} + (ab)^{2} = 2a^{2} + 2b^{2}. 11. (a+b)(ab) = a^{2}  b^{2} 12. (a+b)^{3} = a^{3} + 3a^{2}b + 3ab^{2} + b^{3}. 13. (ab)^{3} = a^{3}  3a^{2}b + 3ab^{2}  b^{3}. 14. a^{3} + b^{3} = (a+b)(a^{2}  ab + b^{2}). 15. a^{3}  b^{3} = (ab)(a^{2} + ab + b^{2}). 16. (a + b + c)^{2} = a^{2} + b^{2} + c^{2} + 2ab + 2bc + 2ca. 17. (a + b  c)^{2} = a^{2} + b^{2} + c^{2} + 2ab  2bc  2ca. 18. (a  b + c)^{2} = a^{2} + b^{2} + c^{2}  2ab  2bc + 2ca. 19. (a  b  c)^{2} = a^{2} + b^{2} + c^{2}  2ab + 2bc  2ca. 20. (a + b + c)(a^{2} + b^{2} + c^{2}  ab  bc  ca) = a^{3} + b^{3} + c^{3} 3abc. 21. (ax + b)(cx + d) = (ac)x^{2} + (ad + bc)x + bd. 22. (x + a)(x + b)(x + c) = x^{3} + (a + b + c)x^{2} + (ab + bc + ca)x + abc. Directions: Choose the correct answer. Also write an example for each of the above formulas. 